The Ethical Life of Health Care Organizations - Reiser, Stanley Joel (The Hastings Center report, 1994)
Institutions have ethical lives and characters just as their individual members do. Health care organizations must look critically at how professed institutional values can best be realized in day-to-day interactions within the institution and with the wider community.